"Gestaltung des Anpassungsdruck", "Rückkehr zu bewährter Gewerkschaftspolitik" oder "Kampf um soziale Transformation"? Gewerkschaftliche Positionen zur Globalisierung in Deutschland und Frankreich - Hürtgen, Stefanie (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The reaction of the left wing of trade unions on the challenges of globalization are rather different in Germany and France, While in Germany the traditional structures of organization are not questioned, only the thinking of the trade union members shall be changed, in France problems are discussed on a more fundamental level, leading - in parts - to new fOrms of organization and trade union policy, seeking the common commitment by neoliberalism in quite different groups,